Determination of Naproxine in its pure form and in some Pharmaceuticals by vis-Spectrophotometry using the Chrome Azrol S - Okdeh , Malek; Dib , Juhaina; Obeid , Mohammad (Latakia University Journal -Basic Sciences Series, 2019)
This study shows the possibility of determining the (NAP) in its pure state and in Pharmaceuticals using Chrome Azrol S Reagent . This spectral method was based on the formation of a colored violet complex at pH=3.5 , The complex has a maximum absorbance value at a wavelength of 545nm. The relationship between absorbance and naproxine concentrations was linear. The Beer-Lambert’s law is within the range of concentrations between (2.306-46.047) µg/ml and with a Relative percentage standard deviation of 1.288 and with a correlation coefficient of R2=0.9987 and a molar absorption coefficient of (1.15×104( L.mol-1.cm-1.The detection limit of naproxen was 0.5873, and the results indicated that the presence of adjuvants does not affect the determination process of naproxen. The analytical results were characterized by a good selectivity, accuracy and sensitivity to the identification of some active substances in its pure state and pharmaceuticals, at a lower cost than the approved constitutional methods